PROBLEMATIKA DALAM SISTEM PENDAFTARAN DOMAIN DAN SISTEM PENDAFTARAN MEREK SERTA PENYELESAIANNYA - Randi Ariadi (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTDomain names even if they are similar to trademarks or services can not be equated. Both of them have substantial differences that allow both to be distinguished, especially in the registration system, their use and the way in which dispute resolution occurs. Although both are different, but the domain name can also get brand-like protection, especially in the domain name as well as the trademark of a company that has entered the category of famous brands. The absence of a domain name setting within the Indonesian national legal system, which governs the domain name itself, or concerns about brand issues. Troubleshooting that occurs in domain name conflicts over brands is done through a conventional ADR or ADRonline agency.